2014
DOI: 10.1111/ijd.12253
|View full text |Cite
|
Sign up to set email alerts
|

Unidentified drugs in traditional medications causing toxic epidermal necrolysis: a developing country experience

Abstract: Illiteracy and financial vulnerability were major factors in driving patients towards the use of traditional medications, which were often prepared and preserved improperly. Mortality and other complications could be reduced by the prompt recognition of the condition, immediate withdrawal of the culprit drug, and quick referral to proper care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Not much is known about the adverse cutaneous side effects of fenugreek intake. A prospective observational study conducted in Bangladesh analyzed a total of 29 patients with TEN admitted to the intensive care unit [27]. In 10 patients (34%), the causative agent remains unidentified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not much is known about the adverse cutaneous side effects of fenugreek intake. A prospective observational study conducted in Bangladesh analyzed a total of 29 patients with TEN admitted to the intensive care unit [27]. In 10 patients (34%), the causative agent remains unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 4 case reports and 1 cohort study including 10 patients [27,28,29,30,31]. In those reports, SJS and TEN were described to be caused by the intake of traditional medications (Chinese roots and drinks), herbal ointment containing realgar and ayurvedic drugs (table 2) [27,28,29,30,31]. In an additional study utilizing large pharmacovigilance data in Thailand from 2002 to 2013, the authors computed that 0.001% of all reported serious adverse drug reactions were due to Thai traditional medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The exact composition of the THM was often unknown. [2][3][4][5][6] The responsibility of the plants could not be confirmed when capsules contained both plant extracts and medicines. 4 Although THM were always suspected, hypersensitivity was not proven in the absence of PT.…”
Section: Referencesmentioning
confidence: 99%
“…4 Although THM were always suspected, hypersensitivity was not proven in the absence of PT. [2][3][4][5][6][7] In cases of generalized erythema multiforme, 8,9 PT with NSO were positive. Our CADRs was probably linked to a substance contained in NSO but its exact composition was unknown.…”
Section: Referencesmentioning
confidence: 99%
“…1 These patients suffer from preexisting psoriasis in about 30% of published cases. 1,6 They tend to be of younger age than those with BP. 3,6 In 2008, Mitsuya et al reported a female patient with metastatic ovarian carcinoma developing subepidermal blistering disease with autoantibodies to p200 and laminin 5.…”
mentioning
confidence: 99%